Exploring the Satire Language Style in the Poem "Aku Berkelana di Udara" by Widji Thukul - Puspita Ningrum (Research in Education, Technology, and Multiculture, 2023)
Abstract: This research was conducted to describe language styles that contain innuendo or criticism that are associated with context in the poem I Wander in the Air by Widji Thukul. The qualitative descriptive method becomes the exact method used in this research, since it focuses on a systematic record with a detailed description of sentences. The reading of the poem "I Traveled in the Air" was done meticulously and carefully for precise data collection techniques. This reseach shows there is a relationship between stylistics and pragmatics that can be used as a study, namely pragmatic stylistics.   Keywords: pragmatic stylistics, satire stylistics, context.